Relação entre habilidades cognitivas e o sistema vestibular em crianças: um estudo transversal - Fontes, Gabriela Eduarda Nicásio Gomes (2025)
Introduction: The vestibular system is composed of several structures, including the labyrinth, which is responsible for maintaining human balance. Individuals with vestibular disorders have difficulties with body balance and other aspects, which can compromise the learning process in children due to changes in the cognitive abilities involved. Thus, vestibular disorders can directly affect children's development and learning. Objective: To investigate the relationship between cognitive abilities and the vestibular system in children. Method: This is an analytical, cross-sectional, and quantitative study conducted with children aged six to 12 years. Cognitive abilities were assessed using the Neupsilin-Inf - Brief Neuropsychological Assessment Instrument for Children. The vestibular system was evaluated using cervical vestibular evoked myogenic potentials (cVEMP) and ocular vestibular evoked myogenic potentials (oVEMP). Data analysis was performed using the t-test for independent samples and the Mann-Whitney test. Results: The sample consisted of 38 children, 21 females and 17 males, with a mean age of 8.7 years. Quantitative analysis indicated significant associations between vestibular assessments and cognitive performance, with emphasis on the relationship between cVEMP amplitude and visual perception ability, as well as between oVEMP asymmetry and memory and executive function skills. Conclusion: The presence of vestibulo-ocular reflex asymmetry in children was significantly related to memory and executive function skills, while a greater amplitude of the vestibulospinal reflex was related to changes in visual perception ability.